The innovative entrepreneur - Spulber, Daniel F. (New York Cambridge University Press, 2014)
The Innovative Entrepreneur presents an economic framework that addresses the motivation of the innovative entrepreneur, the innovative advantage of entrepreneurs versus incumbent firms, the effects of competitive pressures on incentives to innovate, the consequences of creative destruction, and the contributions of the innovative entrepreneur to the wealth of nations"--Provided by publisher.
Keywords: Entrepreneurship; Creative ability in business